Perspectives of school inclusion of learning disorders in high school (Research, Society and Development, 2017)
By being a signatory to the Salamanca Convention of 1994, Brazil has made a commitment to assist students with special educational needs (SEN) and, therefore, we do not need only legislation, but also applicable models. We carried out a review of the literature in search of publications in the last ten years about inclusive practices in high school for these students. It was possible to observe that most of the articles dealing with inclusion focused on Elementary Education, leaving a gap with regard to High School.